Forecasting Electricity Prices in Deregulated Wholesale Spot Electricity Market - A Review - Murthy, Girish Godekere Panchakshara; Sedidi, Vijayalakshmi; Panda, Ajaya Kumar; Rath, Badri Narayan (International Journal of Energy Economics and Policy, 2013)
In the new framework of competitive electricity markets, all power market participants need accurate price forecasting tools. Electricity price forecasts characterize significant information that can help captive power producer, independent power producer, power generation companies, power distribution companies or open access consumers in careful planning of their bidding strategies for maximizing their profits, benefits and utilities from long term, medium term and short term perspective. Short term spot electricity price forecasting techniques are either inspired from electrical engineering literature (i.e. load forecasting) or from economics literature (i.e. game theory models and the time-series econometric models). In this study we investigate the emergence of spot electricity markets with particular emphasis on Indian electricity market which has never been done before and review selected finance and econometrics inspired literature and models for forecasting electricity spot prices in deregulated wholesale spot electricity markets. Keywords: spot price; electricity; forecasting; power market JEL Classifications: C01; C22; C53